PENGARUH SIKAP DAN MOTIVASI TERHADAP PENERAPAN PROGRAM PATIENT SAFETY DI RUMAH SAKIT MEKAR SARI - Oktaviani, Dewi; Kusumapradja, Rokiah; Indrawati, Ratna (Journal of Hospital Management, 2020)
Patient safety has become a global issue that was being hotly discussed throughout the country. The likelihood of accidents in hospitals was much greater than the possibility of an airplane accident, thus proving that Patient safety is a major problem in hospitals all over the world and requires primary attention. To analyze the influence of nurses' attitudes and motivations on the implementation of patient safety programs. This study uses a quantitative approach, survey methods and correlation techniques, the data analysis method used is the multiple linear regression test, the population in this study are nurses who are directly involved in efforts to provide services to patients with a sample of 90 people. The results of this study are attitude variables which have a positive and significant effect on the application of patients safety program at Mekar Sari Hospital. Motivational variables have a negative and insignificant effect on the implementation of the patient safety program at Mekar Sari Hospital. Variables of nurses' attitudes and motivations simultaneously influence the application of patients safety program at Mekar Sari Hospital. suggestions for hospitals Need to be given awards for outstanding nurses and nurses who always implement a patient safety program. As well as periodic / quarterly monitoring and evaluation regarding the implementation of patient safety programs.Keywords: Knowledge about patients safety, attitude, nurse motivation and Patients Safety Program